Ciudad, vecindario y hogar - Carli, César Luis (Buenos Aires : UBA-FADU, 1987)
Notas a propósito del temario del XVI Congreso de la UIA, Brighton, 1987
Keywords: ARQUITECTURA; FORMACION PROFESIONAL; CIUDAD; VIVIENDA; URBANISMO; HABITAT; TEORIA; EDUCACION UNIVERSITARIA